The Effect of the Programmed Education Strategy to Learning the Under Hand Service and Receiving Service Skills of Volleyball for Juniors - Zena Amer Krem; Suhad Qasem saeed Almusawi (Institute of Medico-legal Publications Pvt Ltd, 2021)
In order to advance the education process and raise the educational level of the players, it became necessaryto introduce new educational aids, programmed education in the education process, through which the basicskills to be learned are explained and clarified, and immediate feedback is provided that would enhancethe information of the learner, and Reaching the goal to be achieved, taking into account the individualdifferences between the players, and thus it is possible to move away from the educational methods usedin learning skills, which requires great effort and time, in addition to that the open playground may notperform the skill accurately and the player looks from one side, while when using the computer you lookfrom several sides and at different speeds, as well as you see the best and most accurate performance becauseyou see perfect performance. The aim of the research is the programmed education strategy to learn thetwo skills of sending from the bottom and the skill of receiving the transmission with volleyball emerging,and the researchers used the experimental method of pre and post testing for the experimental and controlgroups, the research population was identified for (24) volleyball players for the 2020 training season, asthe research sample was chosen by a comprehensive inventory method and the sample was divided into twoexperimental groups and the control group, with (12) players for each group, programmed education wasapplied to the experimental group for a period of eight weeks at three training units per week, and they usedthe SPSS statistical bag to process the data and obtain the results, from which the researchers reached themost important conclusions that the programmed education strategy had a positive effect on learning theunder hand service and receiving service skills of volleyball for juniors